Artificial Intelligence (AI) Sebagai Media Pembelajaran pada Anak Usia Sekolah Dasar (6-12 Tahun) (Indo-MathEdu Intellectuals Journal, 2025)
The research aims to find out the extent to which Artificial Intelligence (AI) can be used as an innovative and effective learning medium for children at elementary school age. The research method used is a qualitative approach that is descriptive-interpretive. The type of research used is library research. The data obtained is a descriptive narrative about Artificial Intelligence (AI) as a Learning Media for Elementary School Age Children (6-12 Years Old). The results of the study show that innovative learning media AI offers various advantages and opportunities in the learning process and provides a learning experience. The use of AI-based learning media (Artificial Intelligence) is inseparable from the use of applications/software as tools in learning activities such as kahoot applications, quizizz, google form, tesmoz, ProProfs Quiz Maker and others. The application of AI in education focuses on students who refer to the use of AI technology, a tutor system for adaptive learning that adjusts students' abilities, the use of chatbots, game-based learning, smart course content with AR/VR, data analysis and prediction, and learning evaluation. The use and application of AI has challenges that need to be overcome to maximize its potential in the form of human resource limitations, privacy and security concerns, technology inflexibility, problems with the implementation of AI technology in education, and inequities in cost and access.